Pyrenean meadows in Natura 2000 network: grass production and plant biodiversity conservation - Reiné, Ramón; Barrantes, Olivia; Chocarro, Cristina; Juárez, Alejandro; Broca, Alfonso; Maestro, Melchor; Carlos, Ferrer (Spanish Journal of Agricultural Research, 2014)
In semi-natural mountain meadows, yield and forage quality must be reconciled with plant biodiversity conservation. This study was performed to analyze the relationships between these three parameters. To quantify plant biodiversity and pastoral value (PV), phytosociological inventories were performed in 104 semi-natural meadows in the Central Spanish Pyrenees included in the Natura 2000 network. Forage yields were calculated and forage samples were analyzed for relative feed value (RFV). We identified two main types of meadows: (i) those that had “more intensive management,” relatively close to farm buildings, with little or no slope, dominated by grasses, with low plant biodiversity, high PV and yield, but low forage quality and (ii) those that had “less intensive management,” distant from farm buildings, on slopes, richer in “other forbs”, with high plant biodiversity and forage quality, but low PV and yield. Conservation policies should emphasize less intensive management practices to maintain plant diversity in the semi-natural meadows in the Pyrenees. The widespread view that “other forbs” have low nutritional value should be revised in future research. These species often are undervalued by the PV method, because their nutritional quality, digestibility and intake are poorly understood.